Pemanfaatan Limbah Kulit Buah dalam Menciptakan Inovasi Produk Fermentasi yang Berkelanjutan - I Gede Guna Darmada; Vransisca Sandra; I Made Angga Ferdiawan; I Gusti Ayu Eka Suwintari; Ni Made Ayu Natih Widhiarini (BADAN PENERBIT STIEPARI PRESS, 2025)
Fruit peel waste is one of the most abundant types of organic waste in agricultural areas, including Tambakan Village, located in Kubutambahan District, Buleleng Regency. Until now, fruit peels such as banana, jackfruit, and orange have not been utilized optimally and are often discarded, potentially causing environmental pollution and health risks. This community service program aimed to empower local residents, especially farming groups, to process fruit peel waste into valuable and environmentally friendly fermented products. The program involved several stages, including initial surveys and needs analysis, environmental education and awareness sessions, technical fermentation training, product development mentoring, evaluation, and the creation of a fermentation guidebook. The results showed that participants experienced an increased understanding of organic waste management, gained the ability to independently produce fermented beverages from banana, jackfruit, and orange peels, and demonstrated interest in developing these products on a small-business scale. The fermented products produced have market potential, particularly as functional and eco-friendly beverages. This program successfully fostered sustainable local innovation in organic waste utilization based on village resources.